The centre point of power balancing work and personal life to get to the top, avoid burn-out and make sure you are happy - Farwagi, Peta Lyn (Orion Business, 1998)
Using a combination of philosophical, psychological and practical advice, the author questions the view that one must bow to corporate demands in order to succeed in life, and seeks to redirect the reader by achieving greater balance between their other influences, such as friends, family, hobbies, health and mind.